2015
DOI: 10.1103/physrevc.91.064902
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic field and the chiral magnetic effect in the quark-gluon plasma

Abstract: Time evolution of electromagnetic field created in heavy-ion collisions strongly depends on the electromagnetic response of the quark-gluon plasma, which can be described by the Ohmic and chiral conductivities. The later is intimately related to the Chiral Magnetic Effect.I argue that a solution to the classical Maxwell equations at finite chiral conductivity is unstable due to the soft modes k < σ χ that grow exponentially with time. In the kinematical region relevant for the relativistic heavy-ion collisions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 52 publications
2
90
2
1
Order By: Relevance
“…[26,[93][94][95][96][97] in which the authors studied how the spectators induced magnetic field evolve in QGP phase (assuming the system is already in the QGP phase at the initial time). The main information from these studies are that the presence of the conducting matter can significantly delay the decay of the magnetic field.…”
Section: Recent Quenched Lattice Studies Using Wilson Fermions Obtainmentioning
confidence: 99%
“…[26,[93][94][95][96][97] in which the authors studied how the spectators induced magnetic field evolve in QGP phase (assuming the system is already in the QGP phase at the initial time). The main information from these studies are that the presence of the conducting matter can significantly delay the decay of the magnetic field.…”
Section: Recent Quenched Lattice Studies Using Wilson Fermions Obtainmentioning
confidence: 99%
“…Besides, several possible mechanisms (sources) to increase the photon radiation in heavy ion collisions look quite realistic theoretically but have not been sufficiently definite in phenomenological predictions. One of those mechanisms suggests, for example, that a very strong magnetic field created in noncentral heavy ion collisions can increase the photon radiation owing to the conformal anomaly [15] and synchrotron radiation [16,17]. Another mechanism contributing significantly to the observed anisotropy of direct photons refers to a "magnetic bremsstrahlung-like radiation" (synchrotron radiation in modern terminology) of quarks in the collective color field ensuring a confinement [18].…”
Section: Published By the American Physical Society Under The Terms Omentioning
confidence: 99%
“…For instance, the conductivity has recently been discussed in the context of charge density fluctuations [4] and the evolution of strong electromagnetic fields produced in noncentral collisions [5][6][7][8][9][10]. It has also been suggested that experimental information on conductivity can be extracted from flow parameters in heavy-ion collisions [11].…”
Section: Introductionmentioning
confidence: 99%